Design and implementation of invention learning curriculum-based serious game contents. Issue 3 (3rd July 2019) - Yoon, JunHee; Kim, JungYoon
ABSTRACT: In this paper, invention learning curriculum-based serious game contents were designed and developed. Developed serious game contents evaluated effectiveness among elementary school students with participants classified according to enthusiasm for learning and communication condition for a period of first semester. Existing game-based learning contents tend to give too much importance to learning or amusement which has made it difficult to develop contents. To solve the above-mentioned problems, this study designed and developed serious game which strengthened organic combination between amusement and learning. Serious game contents were designed and developed ways which understand invention principle of curriculum as game play. Evaluation of effectiveness showed that serious game is effective in learning of participants in this study. It was ascertained that students with greater enthusiasm for learning who volunteered invention education course showed better recognition of invention and game than those who studied under general curriculum.